Kesiapan Masyarakat Lokal Nusa Dua Menyambut Era Pariwisata Kenormalan Baru - Ni Putu Dian Utami Dewi; Made Novita Dwi Lestari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
One of the tourism actors that cannot be ignored is the local community. The purposes of this research specifically were to find out 1) the perception of the local community regarding the operation of all hotels in the Nusa Dua Integrated Tourism Area; 2) the readiness of the local community regarding the ‘new normal’ tourism around the Nusa Dua area; 3) preparations made by local communities around the Nusa Dua Integrated Tourism Area to face the new normal tourism. This study used a quantitative approach. Respondents for this activity were 100 men and women of productive age between 23-45 years who came from around the Nusa Dua Integrated Tourism Area. The positive attitude shown by the local community is because 55% of the respondents stated that new normal tourism is safe tourism for all tourism actors. As many as 85% of respondents stated their readiness if tourism in their area was opened and only 10% stated that they were not ready. Some 65% of respondents are preparing to work again in the tourism sector. Keywords: local community, new normal tourism, readiness.